New Sandwich and Half-Sandwich Titanium Hydrazido Compounds - Selby, J; Feliz, M; Schwarz, A; Clot, E; Mountford, P (2011)
New mono- and bis-cyclopentadienyl terminal titanium hydrazido(2-) compounds were prepared by tert-butyl imide/N,N-disubstituted hydrazine exchange reactions. Reaction of Cp*Ti(NtBu)Cl(py) (1) with Ph 2NNH2 gave the terminal hydrazide Cp*Ti(NNPh 2)Cl(py) (4), whereas the corresponding reaction of CpTi(N tBu)Cl(py) gave the dimer Cp2Ti2(μ- η1:η1-NNPh2)(μ-η2: η1-NNPh2)Cl2. Reaction of 1 with Me 2NNH2 (1 equiv) also gave a dimer, Cp* 2Ti2(μ-η1:η1-NNMe 2)(μ-η2:η1-NNMe2)Cl 2 (8), while the reaction with 2 equiv of Me2NNH 2 gave Cp*Ti(η2-NHNMe2)2Cl (7) containing two η2-bound hydrazide(1-) ligands. Formation of 7 and 8 proceeds via a common intermediate, Cp*Ti(NHtBu) (η2-NHNMe2)Cl, observed by NMR spectroscopy. Reaction of 4 with LiNHNPh2 gave the mixed hydrazide(2-)/hydrazide(1-) derivative Cp*Ti(NNPh2)(NHNPh2)(py) (10). The corresponding reaction of 1 formed Cp*Ti(NtBu)(NHNPh 2)(py), which rearranged to Cp*Ti(NHtBu)(NNPh 2)(py). The titanocene derivative Cp2Ti(NNPh 2)(py) (14) was prepared by reaction of Cp2Ti(N tBu)(py) (13) with Ph2NNH2, whereas the corresponding reaction with Me2NNH2 gave mixtures including CpTi(NHtBu)(μ-η1:η1- NNMe2)(μ-η2:η1-NNMe 2)TiCp(η1-Cp). The electronic structure of 14 was investigated by DFT and compared to that of the imido complex 13. Whereas the HOMO of the formally 20 valence electron compound 13 is a ligand-centered orbital based both on the Cp rings and on the imido N, in 14 this is the HOMO-1 and one of the Ti=Nα π-bonding MOs is the HOMO, destabilized by an Nα-Nβ antibonding interaction. © 2011 American Chemical Society.